Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd004690.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy for anxiety disorders in children and adolescents

Abstract: Cognitive behavioural therapy is an effective treatment for childhood and adolescent anxiety disorders; however, the evidence suggesting that CBT is more effective than active controls or TAU or medication at follow-up, is limited and inconclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
154
2
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(177 citation statements)
references
References 127 publications
7
154
2
9
Order By: Relevance
“…Cognitive behaviour therapy (CBT) is an effective treatment (Cartwright-Hatton, Roberts, Chitsabesan, Fothergill, & Harrington, 2004;Compton et al, 2014;James, James, Cowdrey, Soler, & Choke, 2013); however, it typically requires specialist resources and is often not available to those who might benefit from it (Stallard, Udwin, Goddard, & Hibbert, 2007).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…Cognitive behaviour therapy (CBT) is an effective treatment (Cartwright-Hatton, Roberts, Chitsabesan, Fothergill, & Harrington, 2004;Compton et al, 2014;James, James, Cowdrey, Soler, & Choke, 2013); however, it typically requires specialist resources and is often not available to those who might benefit from it (Stallard, Udwin, Goddard, & Hibbert, 2007).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…Overall reviews and meta-analyses have indicated that programs in which parents of anxious children are incorporated into the treatment result in no greater efficacy than programs targeting the child alone (In-Albon and Schneider 2006;James et al 2006). However, these reviews do not typically consider differences in age of the child, and in fact, there are few studies that either include a sufficient age range or have sufficient power to detect relevant differences (Creswell and Cartwright-Hatton 2007;Rapee et al 2009).…”
Section: Importance Of Including Families In Treatment For Child Anxietymentioning
confidence: 99%
“…Generally, CBT for CADs has been found to have a large pre-post effect size (e.g., ES = 0.86;In-Albon and Schneider 2007) and moderate response rate (e.g., 56 %; James et al 2009). However, CBT has not demonstrated superiority over active controls or treatment as usual (Barrington et al 2005;James et al 2013;Southam-Gerow et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, CBT for CADs has been found to have a large pre-post effect size (e.g., ES = 0.86;In-Albon and Schneider 2007) and moderate response rate (e.g., 56 %; James et al 2009). However, CBT has not demonstrated superiority over active controls or treatment as usual (Barrington et al 2005;James et al 2013;Southam-Gerow et al 2010). For example, in the largest RCT for CADs, CBT using the AMSEx model was more effective than pill placebo, but did not differentiate from medication, was less effective than combined treatment, and led to remission rates below 50 % (Ginsburg et al 2011;Walkup et al 2008).…”
Section: Introductionmentioning
confidence: 99%